Analysis of Electrical DNA Biosensor For Human Papillomavirus (HPV) Strain 18 Detection in Synthetic and Saliva Samples - Mohamad Amirul Mhd Akhir (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To inspect the morphology of gold IDE on the DNA biosensor for perfect alignment and to ensure the functional of device by using SEM. To set up surface modification by dropping APTES solution on the surface of DNA biosensor for perfect attachment of bio-molecule for immobilization process. To examine the operational of electrical DNA biosensor through hybridization of DNA probe and DNA target by using current voltage characterization.